The relationship between intrinsic spirituality, resilience and hopelessness in patients with epilepsy: A PATH analysis - Basak, Seda; Turan, Gulcan Bahcecioglu; Ozer, Zulfunaz; Tan, Mehtap (Academic Press Inc Elsevier Science, 2025)
Background: This study was conducted to examine the relationship between intrinsic spirituality, resilience and hopelessness in patients with epilepsy and to investigate the mediating role of resilience in the relationship between intrinsic spirituality and hopelessness. Methods: This study is a descriptive correlational research. The study was conducted with 120 patients who met the inclusion criteria between January 2023 and July 2023. Data were collected by using Personal Information Form, Intrinsic Spirituality Scale (ISS), Beck Hopelessness Scale (BHS) and Brief Resilience Scale (BRS). Results: According to the results of the study, it was found that the mean ISS score (beta = 0.730) affected the mean BRS score positively and the mean BHS score (beta = -0.497) negatively (p > 0.05). It was found that the mean BRS score affected the mean BHS score (beta = -0.178) negatively (p > 0.05). The indirect effect (beta = -0.129) and total effect (beta = -0.626) of intrinsic spirituality on hopelessness mediated by the mean BRS score were found to be negative and significant. It was determined that the tested model provided a good fit and explained the direct and indirect effects of the study variables. Conclusion: According to the results of the study, it was found that intrinsic spirituality affected resilience positively and hopelessness negatively. Resilience was found to have a negative effect on hopelessness. It was determined that resilience partially mediated the relationship between intrinsic spirituality and hopelessness and this situation reduced hopelessness more.
Keywords: Epilepsy; Intrinsic spirituality; Resilience; Hopelessness